Imaging and Minimally Invasive Biopsy for Postmortem Pulmonary Fat Embolism Diagnosis - Liauw Djai Yen; Clara Valentina J; Gabriella Hamid; Mutiara Jesslyn Taslim; Leonardo Leonardo; Florentina Reddy; Oscar Odillo Laman; Maria Zita (Faculty of Medicine, Universitas Padjadjaran, 2021)
In recent years, imaging technologies and minimally invasive biopsy have been gaining importance in forensic settings. This study aimed to evaluate the role of imaging and minimally invasive biopsy in postmortem diagnosis of pulmonary fat embolism. This was a systematic literature review by using Pubmed, EBSCO-Host, and ProQuest to search for studies on postmortem diagnosis of pulmonary fat embolism with postmortem imaging and minimally invasive biopsy. Five studies were included in the systematic review. These studies employed the following diagnostic technics: postmortem computed tomography (PMCT), postmortem computed tomography angiography (PMCTA), percutaneous needle biopsy (PNB), postmortem magnetic resonance (PMMR), and traditional autopsy. Imaging and minimally invasive biopsy are potential modalities that might complement or even replace traditional autopsy in diagnosing PFE. Further studies are needed to confirm the sensitivity and specificity of each technique.